Treatment and outcome in combined scapula and rib fractures. (1st June 2022) - Hoepelman, R; Beeres, F; van Veelen, N; Houwert, M; Babst, R; Link, B-C; van de Wall, B
Abstract: Objective: The primary aim was to describe the population characteristics of patients with combined scapula and rib fractures and outcomes associated with different treatment strategies. Secondarily, a systematic literature review was conducted to provide an overview of the available literature on this population. Methods: All adult (≥18 years) patients with concurrent ipsilateral scapula and rib fractures admitted to the study hospital between 1st January 2010 and 31st June 2021 were retrospectively reviewed. Secondarily, the Pubmed, EMBASE and CENRTAL databases were searched to identify studies reporting on this patient population. Results: A total of 243 patients were admitted with concurrent ipsilateral rib and scapula fractures. 160 patients (72%) were treated conservatively, 63 patients (28%) operatively. Among operatively treated patients, 32 (51%) underwent rib fixation (RF) only, 24 (38%) underwent scapula fixation (SF) only and 7 patients (11%) underwent combined fixation of scapula and ribs (SRF). In general, more severely injured patients were treated with more extensive surgery. RF patients had a median hospital length of stay of 16 days, the SF patients 11 days and SRF patients 18 days. There were no significant differences in complications (pneumonia, recurrent pneumothorax, and revision surgery) between groups. The systematic review included 9 studies of which none reported on outcomes or treatment strategy for this combined injury. Conclusion: Injury severity resulted in different treatment modalities. As a result different patient characteristics between treatment groups were observed, which makes direct comparison between treatment modalities impossible. All treatment modalities seem feasible, however the additional value of both rib and scapula fixation has yet to be proven in large multicentre studies.